The Link Between Anxiety and Depression, and Balance in Young Adults - Tatiana Marques; Patrícia Bernardo; Margarida Serrano (Audiology Research)
Background/Objectives: The ability of young adults to control their balance is generally effortless and can occur automatically with minimal cognitive involvement. However, this ability may be compromised when integration conflicts arise due to impairments in vestibular, visual, or somatosensory functions. Hence, psychomotor symptoms linked to emotional states can also influence postural control. The purpose of this study was to understand the effects of anxiety and depression on balance in young adults. Methods: Our study included 50 young adults (21.86 ± 2.63 years), consisting of 13 males and 37 females. Anxiety and depressive symptoms were evaluated using the Hospital Anxiety and Depression Scale (HADS), while balance was assessed through the Modified Clinical Test for the Sensory Interaction on Balance (mCTSIB). Data analysis was conducted using Pearson’s correlation coefficient test and the Kruskal–Wallis test. Results: Pearson’s correlation analysis indicated that young adults exhibited stable postural control. However, a positive correlation (0.259, p < 0.1) was observed between anxiety levels and the sway index. Additionally, positive correlations were found between anxiety and both somatosensory (0.281, p < 0.05) and visual (0.276, p < 0.1) ratios. Conclusions: The results suggest that higher anxiety levels are associated with reduced postural balance, with sensory inputs, particularly visual and somatosensory, playing a key role in this decreased stability.